2002
DOI: 10.1016/s0002-9440(10)64415-x
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of Platelet-Derived Growth Factor or Its Receptors Transiently Delays but Does Not Prevent Fibrous Cap Formation in ApoE Null Mice

Abstract: Platelet-derived growth factor (PDGF) is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
68
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(76 citation statements)
references
References 69 publications
7
68
1
Order By: Relevance
“…In cultured SMCs, PDGF-BB represses expression of multiple SMC differentiation marker genes and coordinately increases SMC proliferation, migration, and matrix synthesis, consistent with SMC phenotypic modulation to a synthetic state (2,4,7,26,34). In addition, in vivo blockade of PDGF-BB or PDGFR-␤ reduces SMC migration into neointimal lesions after vascular injury and decreases SMC accumulation and fibrous cap formation within developing atherosclerotic plaques in mice (25,37,54,66,69). Recent studies have demonstrated that PDGF-DD, a newly discovered PDGF isoform that is a more selective agonist of the PDGFR-␤, also promotes SMC phenotypic modulation through repressing SMC differentiation marker gene expression and increasing SMC proliferation and migration (5,13,38,73).…”
mentioning
confidence: 70%
See 1 more Smart Citation
“…In cultured SMCs, PDGF-BB represses expression of multiple SMC differentiation marker genes and coordinately increases SMC proliferation, migration, and matrix synthesis, consistent with SMC phenotypic modulation to a synthetic state (2,4,7,26,34). In addition, in vivo blockade of PDGF-BB or PDGFR-␤ reduces SMC migration into neointimal lesions after vascular injury and decreases SMC accumulation and fibrous cap formation within developing atherosclerotic plaques in mice (25,37,54,66,69). Recent studies have demonstrated that PDGF-DD, a newly discovered PDGF isoform that is a more selective agonist of the PDGFR-␤, also promotes SMC phenotypic modulation through repressing SMC differentiation marker gene expression and increasing SMC proliferation and migration (5,13,38,73).…”
mentioning
confidence: 70%
“…Indeed, as opposed to our observation of overrepresentation of NF-B binding sites in distinctly IL-1-induced genes, genes distinctly induced by PDGF-DD exhibited overrepresentation of binding sites for E2F family members (Table 5), which are known regulators of cell proliferation (3,24). As such, it is interesting to postulate that it may be feasible to therapeutically target NF-B to selectively inhibit transition of SMC to an inflammatory state while retaining a PDGF-induced proliferative SMC phenotype that may contribute to plaque stabilization through enhancing SMC accumulation within plaques and formation of a protective fibrous cap (37,66).…”
Section: Discussionmentioning
confidence: 99%
“…Restenosis following angioplasty of atherosclerotic vessels in minipigs (Bilder et al 1999) and chronic cardiac transplant rejection-induced atherosclerosis in rats (Sihvola et al 1999) were also inhibited by PDGFR-blocking kinase inhibitors. In ApoE-deficient mice, atherosclerotic lesions were inhibited by neutralizing PDGFR-␤ antibodies (Sano et al 2001) and a PDGFR blocking kinase inhibitor (Kozaki et al 2002). Conversely, infusion of PDGF-BB (Jawien et al 1992) or local transfection of a PDGF-B expression vector (Nabel et al 1993) led to increased SMC proliferation and intima thickening in certain models of arterial injury.…”
Section: Atherosclerosis and Restenosismentioning
confidence: 99%
“…This suggests impaired migration of vSMC from the media to the intima in the absence of functional PDGFR-␤ (Buetow et al 2003). Another type of chimeric situation was obtained by bone marrow transplantations of PDGF-B-deficient marrow into lethally irradiated, ApoE-deficient recipients (Kozaki et al 2002). The lack of PDGF-B production by infiltrating inflammatory cells led to a small and transient inhibition of neointimal fibrous cap formation.…”
Section: Platelet-derived Growth Factor Genes and Development 1295mentioning
confidence: 99%
“…PDGFR ligation is generally pro-proliferative and antiapoptotic (in part through PKB and ERK activation) as well as anti-inflammatory and profibrotic. In one study, transplant of PDGF-B-null fetal liver cells into irradiated ApoE Ϫ/Ϫ mice resulted only in a delay of VSMC accumulation and fibrous cap formation without a change in lesion volume (945). In addition, macrophages appeared more inflammed or activated in the PDGF-B-null chimeric mice.…”
Section: Newer Insights Into the Role Of Vsmc In Atherosclerosismentioning
confidence: 99%